2016
DOI: 10.1097/rlu.0000000000001124
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Evidence of Effective Treatment of Cardiac Sarcoidosis With Adalimumab

Abstract: A 53-year-old man with mediastinal lymph node biopsy and cardiac MRI-proven cardiac sarcoidosis (CS) received treatment with pacemaker and steroids. FDG PET/CT showed active CS despite treatment with prednisone and methotrexate. Addition of weekly adalimumab (Humira) injections was introduced for 3 months. Follow-up FDG PET/CT showed complete resolution of CS as well as improvement of other sarcoid lesions in the thoracic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…However, decreased perfusion at rest is not specific nor sensitive for CS diagnosis; many CS can have normal or even increased perfusion. Our experience also showed that, with optimal suppression of physiologic myocardial 18 F-FDG uptake, the rest myocardial perfusion study or reorientation/reconstruction of cardiac 18 F-FDG PET/CT images might not be needed (4,5). The authors recommended interpretation of concurrent myocardial perfusion and 18 F-FDG PET images mainly based on the data from Brigham and Women's Hospital, which included 118 patients over a 5-y period who underwent ,24-h HFHPVLC diet followed by a fast of at least 3 h before 18 F-FDG PET and 82 Rb myocardial perfusion PET (6).…”
Section: Referencesmentioning
confidence: 89%
“…However, decreased perfusion at rest is not specific nor sensitive for CS diagnosis; many CS can have normal or even increased perfusion. Our experience also showed that, with optimal suppression of physiologic myocardial 18 F-FDG uptake, the rest myocardial perfusion study or reorientation/reconstruction of cardiac 18 F-FDG PET/CT images might not be needed (4,5). The authors recommended interpretation of concurrent myocardial perfusion and 18 F-FDG PET images mainly based on the data from Brigham and Women's Hospital, which included 118 patients over a 5-y period who underwent ,24-h HFHPVLC diet followed by a fast of at least 3 h before 18 F-FDG PET and 82 Rb myocardial perfusion PET (6).…”
Section: Referencesmentioning
confidence: 89%
“…Until 2019, there were no randomized trials on TNFα antagonists in CS, and only a few cases reports or series had shown the potential benefit of TNFα antagonists (17)(18)(19)(20)(21)(22). The ATTACH (Anti-TNF Therapy Against Congestive Heart Failure) trial (34) found worsening of heart failure in patients treated by high-dose infliximab for congestive heart failure with other causes than sarcoidosis limiting its use in cardiac inflammatory conditions such as CS.…”
Section: Discussionmentioning
confidence: 99%
“…In severe or refractory disease, TNFα antagonists are effective in ocular (13), neurological (14), osseous (15), and pulmonary (16,17), sarcoidosis. In CS, a few cases reports (18)(19)(20)(21)(22) and five cohort studies (23)(24)(25)(26)(27) have shown benefits of CT with or without IT in patients with severe and/or refractory cardiac involvement. Although there has been no randomized controlled study, some articles and expert opinions have suggested that TNFα antagonists for severe or refractory CS might be an option in case of CT or IT failure (28-30).…”
Section: Introductionmentioning
confidence: 99%
“…However, disease remained refractory to all these agents and resolved with anti-TNF therapy (adalimumab). TNF-alpha plays an important role in the genesis and perpetuation of granulomas, and its inhibitors have been utilized in the management of refractory sarcoid 10, 11. To the best of our knowledge this is the first case of refractory VT in CS, successfully managed with anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%